E-Abacus animator / Lim Chun Yit - Lim , Chun Yit (2005)
E-Abacus Animator is a web-based teaching-learning tool that is aimed at providing users with all possibilities to learn and teach mental arithmetic with an abacus like the E-Learning system. An abacus is a culculating instrument with a number of beads sliding back and forth along rods, for doing and teaching arithmetic. Mental arithmetic is the way to do math in our head without any pencil and paper. It can be make our get clearer picture for the arithmetic problem. E-Abacus Animator will be provides skills, examples, tutorials and tests for each arithmetic operation to make sure the user get the clear understanding for the arithmetic problem by using the Abacus. E-Abacus Animator is divided into two parts: user homepage and administrator homepage. The user homepage provides all possibilities for learning and teaching mental arithmetic with an abacus, and provides strategies, examples, tutorials for each arithmetic operation. It provides the following functions:. Lessons learning: consists of 5 sections comprising of a simulated abacus for calculation and 4 lessons for reading an abacus, addition, subtraction, multiplication, division and combined operation. The administrator homepage allows the administrator to maintain all step of the examples, tutorials and test questions at the back-end database system. It provides the following functions: Administrator authorization: to check the authorizations to access the administrator homepage. · Question module: consists of 4 sections comprising of earch, add and delete, for maintaining the questions and answers and steps in the database. This report provides an overview for the -Abacu nimat raft r make some enhancements. The enhancements provide a hamepage and the database.The main objective of this system is introduce a database system to assist the system. After the enhancement, it divides into two categories. (the administrator part and a user part) E-Abacus Animator system is implem nted b using the development tool which is Microsoft Visual Studio .NET 2003 in this case.